Evolution of gynoecium morphology in old world papaveroideae: a combined phylogenetic/ontogenetic approach - Kadereit, Joachim W.; Erbar, Claudia (American journal of botany, 2011)
Premise of the study: The correct assessment of homology is an important prerequisite for reconstructing phylogenetic relationships and character evolution. Old World Papaveroideae (Papaver, Meconopsis, Roemeria, Stylomecon) show substantial diversity in gynoecium and capsule morphology. In particular, capsules can have distinct styles (Meconopsis p.p., Stylomecon) or a sessile stigmatic disc (Papaver). Molecular phylogenetic analyses of Old World Papaveroideae had shown that neither taxa with styles nor those with stigmatic discs represent monophyletic lineages. We here investigate whether either styles or stigmatic discs have arisen repeatedly during the diversification of Old World Papaveroideae. Methods: We investigated gynoecium ontogeny in Papaver rhoeas, P. californicum, Meconopsis cambrica, and Stylomecon heterophylla by scanning electron microscopy for the first time. Our observations were interpreted on the background of a well-resolved molecular phylogeny of the taxa investigated. Key results: Papaver rhoeas and P. californicum share the presence of a developmentally complex garland-like stage in gynoecium ontogeny. The styles of M. cambrica and S. heterophylla result from growth in a ring-like zone beneath the carpel tips. This zone is also present in Papaver. In M. cambrica, traces of a garland-like stage can be seen. Style formation and stigma formation begin more or less simultaneously in M. cambrica, but style formation clearly precedes stigma formation in S. heterophylla. Conclusions: The styles present in M. cambrica and S. heterophylla are considered to have arisen in parallel from ancestors with a stigmatic disc. We speculate that style formation may have been a means to reduce selfing.
Gesehen am 10.05.2017